Factors of Workplace Happiness: A Systematic Literature Review (International Journal of Innovative Research in Engineering & Management, 2021)
Happiness, defined as pleasurable feelings and sensations,  well-being, and good attitudes, has gotten a lot of interest in  psychological studies recently. The pursuit of joy has spilled  over into the job. This study summarizes what is recognized  more about definitions, origins, and effects of workplace  pleasure, as well as ideas from the growing favourable psychological research on pleasure in general. Many distinct  term organisational components, in my opinion, are part of a  wider family of pleasure concepts that have certain similar  origins and outcomes. Job fulfilment is a part of happiness at  profession, but it's not the whole story. Professional  engagement, work performance, and emotional corporate  citizenship behavior may indeed be included in a complete  assessment of personal joy. At numerous layers, encompassing  ephemeral emotions, permanent character views, and  communal behaviours, and with regard to different emphases,  such as particular units, the work, and the organisation,  components of pleasure have been (and should be) conceived  and quantified. There is information that pleasure has  significant repercussions for both people and institutions at all  levels. Previous studies has been able to undervalue the  relevance of workplace enjoyment.
Keywords: Happiness; Human; Organization; Responsibilities; Workplace